Predictive factors for treatment success of epidural steroid injections in patients with lumbar spinal surgery - KOKAR, SERDAR; GÜNDÜZ, OSMAN HAKAN (My University, 2023)
OBJECTIVE: The efficacy of epidural steroid injections (ESIs) in the treatment of radicular pain in patients undergoing lumbar spinal surgery is still unclear. The aim of this study was to investigate the factors affecting the success of ESIs in the treatment of ongoing radicular pain in patients undergoing lumbar spinal surgery. PATIENTS AND METHODS: This study was designed as a single-center, retrospective study, and was conducted at a Pain Management Center of a tertiary care center. A total of 260 patients with failed back surgery syndrome who received fluoroscopy-guided lumbar ESI were included. Treatment success was defined as ≥50% reduction in the numeric rating scale score at the one-month follow-up. The patients were divided into the treatment success and the treatment failure groups. RESULTS: The presence of spinal instrumentation was significantly lower in the treatment success group (p=0.045). Symptom duration and the numeric rating scale score at 1 hour were significantly lower in the treatment success group (p<0.05). The use of triamcinolone acetonide in the treatment success group was found to be significantly higher than in the treatment failure group (p=0.027). CONCLUSIONS: The short duration of symptoms and the absence of instrumentation seem to be prognostic factors that positively affect the success of ESI treatment in operated patients. A ≥50% pain reduction in the first hour after the procedure is a valuable indicator that treatment success can be achieved in the short term. Finally, the steroid type can also affect the treatment results.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Farmakoloji (tıbbi); Pharmacology (medical); y Words: Epidural Injections; Lumbar spinal surgery; Failed back surgery syndrome; Lumbar radicular pain